No lixo? Na Arte?: um estudo da consciência política dos sujeitos participantes em empreendimentos de economia solidária em Tangará da Serra-MT - Junior, Wilson Luconi (Universidade do Vale do Rio dos Sinos, 2011)
The dissertation discusses the solidary economy with focus on political awareness of individual participants in the social economy enterprises. It describes and analyzes this political consciousness through seven dimensions as proposed by Sandoval (1994), like: the collective identity issue; beliefs, values and expectations; conflicting interests and opponents; political effectiveness; justice and injustice feelings; wish of acting collectively and the social movement actions and aims. It was presented some theoretical articulations of the solidarity economy to contribute to this discussion, the question on the understanding of the subjetct, some theories on social movements and, finally, on political consciousness. The research consists in an exploratory case study, whose data were collected through individual interviews, focus groups and observations. The selected groups were: Coopertan - Production Cooperative of Recyclable Material of Tangara da Serra, MT and Artetan - Craftsmen Association of Tangara-MT. The analysis consisted of categorizing the speeches by the dimensions of the political consciousness. The results indicate that the enterprises are a possible space of politicizing the survival, through self-management and training; identities are often constructed through relations of kinship and freedom at work and the struggle of cooperative members is against the capitalist system, that excludes them from the labor market. Also indicate there are, in enterprises, spaces of support and solidarity. This essay which shares the own life has presented policy formation aspects, i.e., a politicization of and for the survival.
Keywords: Economia solidária; Trabalho; Consciência Política; Catadores; Artesãos; Solidary economy; Work; Political consciousness; Scavengers; Craftsmen; ACCNPQ::Ciências Humanas::Sociologia